The Serabit Expedition of 1930: I. Introduction - Lake, Kirsopp (Harvard theological review, 1932)
One of the incidental, but, as it proved, important results of the Harvard Expedition to Mount Sinai in 1927 was the rediscovery of the Sinaitic inscriptions on Serabit el-Khadim, a desolate mountain in the interior of the peninsula, rendered famous by the ruins of a temple of the Egyptian goddess Hathor and by many exhausted turquoise mines.